The VIPR-1 trial (Visualizing Ischemia in the Pancreatic Remnant): Assessing the role of intraoperative indocyanine green perfusion in predicting postoperative pancreatic leaks and fistulas: Protocol for a phase II clinical trial - Gustavo Salgado-Garza; Annika Willy; Flavio G. Rocha; Skye C. Mayo; Brett C. Sheppard; Patrick J. Worth (PLoS ONE, 2025)
Surgery of the pancreas has come a long way since its inception; however, postoperative morbidity is still high. Pancreatic leaks and fistulas are common complications in patients undergoing surgery to remove the pancreas. Fistulas delay subsequent oncological care after surgery and prolong the hospital stay. Hypoperfusion of the pancreas has been proposed as one factor leading to fistulas. Indocyanine green (ICG) injection allows the surgeon to evaluate blood perfusion to tissue in real-time. This protocol describes a trial that aims to assess the effectiveness of intraoperative ICG metrics of the cut edge of the remnant pancreas to predict postoperative fistulas. A single group will participate in an observational, surgeon-blinded, phase II trial. ICG measurements of the cut edge of the pancreas will be recorded before reconstruction. International Study Group on Pancreatic Surgery criteria for pancreatic fistula will be used to define leaks and fistulas. The study objective is to analyze the correlation between ICG measurements and the development or absence of both biochemical leak and clinically relevant fistula formation. Currently, limited objective intraoperative predictors exist for predicting postoperative fistulas. Having a reliable predictive tool could decrease the healthcare burden posed by fistulas. The findings of this trial will provide conclusions on the usefulness of ICG measurements in predicting postoperative pancreatic fistulas and leaks. This clinical trial is registered in ClinicalTrials.gov with the ID NCT06084013. The current protocol version is v1.1.